Study on the Thermophysical Properties and Influencing Factors of Regional Surface Shallow Rock and Soil in China - Zhu, Xi; Gao, Zongjun; Chen, Tao; Wang, Wanli; Lu, Chuan; Zhang, Qinglian (Frontiers in Earth Science, 2022)
Thermophysical properties of rock and soil are important parameters that affect the efficiency of shallow geothermal energy utilization. This paper analyzes the thermophysical parameters (specific heat capacity and thermal conductivity) and their influencing factors based on 6467 sample data in 24 provincial capitals, China. The statistical distributions of thermophysical properties are analyzed based on histogram plots. Linear regression analysis is conducted to investigate the correlation between thermophysical properties and lithology (classified as metamorphic rocks, igneous rocks, chemical sedimentary rocks, clastic sedimentary rocks, and loose sediments in this study)), density, and water content. The results show that the thermophysical properties are influenced predominantly by lithology. The measured values of thermophysical properties of different rock and soil generally show normal distribution characteristics. The specific heat capacity of loose sediments is relatively high, the thermal conductivity of other 4 types are relatively high. The specific heat capacity is negatively correlated with density, positively correlated with water content, whereas thermal conductivity is positively correlated with density, and negatively correlated with water content. The findings obtained in this study provide evidence and guidelines for the investigation, evaluation, and development of shallow geothermal resources.